146k views
2 votes
Which expressions are equivalent to 5+(−3)(6x−5)

Choose all answers that apply:


A
18x−20


B
3x-3


C
None of the above

2 Answers

4 votes

Answer:

none of the above

Explanation:

just for people who dont want one

User CharliePrynn
by
4.8k points
5 votes

Answer:

C. None of the above

Explanation:


5+(-3)(6x-5)\qquad\text{use the distributive property}\ a(b+c)=ab+ac\\\\=5+(-3)(6x)+(-3)(-5)\\\\=5-18x+15\qquad\text{combine like terms}\\\\=-18x+(5+15)\\\\=-18x+20

User Jq Beginner
by
4.8k points